Geomorphologic Map of Northeastern Sector of San Jorge Gulf (Chubut, Argentina) - Isola, Ilaria (2011)
This paper presents a 1:100,000 scale geomorphologic map of the Northeastern sector of San Jorge Gulf (Chubut Province) in Patagonia, Argentina, covering more than 1,000 km2. Derived from remote sensing data and validated by three field surveys, it has been compiled in order to understand the past and recent evolution of the area with particular reference to sea-level oscillation studies, for which this map is the basic tool. The very low human impact and rates of dynamic landscape change allow the preservation of extensive palaeo deposits and landforms, including those indicative of sea-level variations. The relative change of sea level dominates landscape evolution, allowing the formation of widespread marine and lagoon deposits often interfingering with fluvial deposits and reworked by aeolian process in the framework of consequent beach progradation.